Weight Loss and Transient LDL Increase (P12-057-19). (13th June 2019) - Surampudi, Vijaya; Biggs, Katherine; Li, Zhaoping
Abstract: Objectives: Very low calorie diets have been utilized for weight loss and glycemic control for several decades. In addition, improvements in blood pressure and cholesterol have been observed but few have reported the change in metabolism of lipoproteins (HDL, LDL and triglycerides (TGs)) during the weight loss process. Several cases have demonstrated the dynamic nature of lipoprotein metabolism during intensive weight loss program. Methods: Patients were enrolled in self-paid university based medical weight loss program utilizing a VLCD (500–800 calories) program. In addition, patients were recommended to exercise and participate in group cognitive behavioral counseling. During the program patients CBC, CMP and Lipid panel were monitored. In the following three cases of patients utilizing the VLCD averaging about 800 calories the following changes in lipids were noted. All patients were noted to have improved in triglycerides and HDL. Case #1: 48 y/o male whose baseline weight was 267 lbs with BMI 38 kg/m 2 who lost 55 lbs over 5 months and with the lowest weight of 202 lbs and BMI of 29 kg/m 2 . Over this time LDL baseline was 143 mg/dL improving to 52 mg/dL but later increasing to 178 mg/dL and 6 weeks later normalizing to 72 mg/dL. Case #2: 70 y/o female whose starting weight was 217 lbs with BMI 38 kg/m 2 who lost 41 lbs over 5 months and with the lowest weight of 176 and BMI of 31 kg/m 2 . Over this time LDL baseline was 108 mg/dL but later increasing to 157 mg/dL and 12 weeks later normalizing to 111 mg/dL. Case #3: 55 y/o female whose starting weight was 245 lbs with BMI 39.56 kg/m 2 who lost 79 lbs over 8 months and with the lowest weight of 166 lbs and BMI of 26.9 kg/m 2 . Over this time LDL baseline was 93 mg/dL but later increasing to 136 mg/dL and 12 weeks later normalizing to 108 mg/dL. Results: These observations suggest change in the metabolism of lipoproteins, namely by decreasing triglycerides, increasing HDL, and increasing the fraction of large particle-size LDL. A limitation of the LDL measurement is that it is a calculated measurement not taking into account the varying sizes of LDL. More small dense LDL equates to higher risk in coronary artery disease however in the calculated method the size is unclear. Conclusions: In these cases we observed a transient increase in LDL however size of LDL measured is unknown. Therefore, any concern about the long-term effects of VLCDs on cardiovascular health will need further prospective studies to help elucidate lipid metabolism as people lose weight. Funding Sources: UCLA - Department of Medicine Clinical Nutrition.